Peri-renal fat thickness is positively associated with the urine albumin excretion rate in patients with type 2 diabetes. Issue 4 (July 2020) - Shen, Feng-Chih; Cheng, Ben-Chung; Chen, Jung-Fu
Abstract: Backgrounds: Albuminuria, the earliest clinical manifestation of diabetic kidney disease (DKD), is a major prognostic indicator of renal progression. Obesity itself is associated with the development of DKD and accelerates its progression. Accumulation of peri-renal fat on the kidneys can damage kidney function. Measuring the perirenal fat thickness (PFT) by ultrasound is a non-invasive method to measure ectopic fat deposition on the kidney. In this study, we aim to obtain the association between albuminuria and PFT. Methods: Eighty-nine subjects with type 2 diabetes mellitus (T2DM) were enrolled. Albuminuria was defined as a urine albumin-to-creatinine ratio (UACR) ≧30 mg/g. Measurement of the PFT was performed by B-mode ultrasound (Toshiba SSA-680A) and determined from the surface of the abdominal musculature to the surface of kidney. Pearson correlation coefficients were determined to test the significant independent relationship between the PFT and demographic, anthropometric and laboratory parameters. Results: Patients were divided into those with (n = 66) and without (n = 23) albuminuria. PFT (odds ratio [OR], 19.3; 95% CI, 2.25–165.00; p = 0.01) was significantly correlated with albuminuria based on multiple logistic regression analysis. Additionally, linear regression confirmed that degree of albuminuria has a positive association with the PFT (r = 0.233; p = 0.03). Conclusions: Our study showed that an increased PFT is positively associated with the albuminuria among patients with T2DM. Our findings suggest that measurement of the PFT may represent a helpful tool to assess the risk of developing albuminuria in patients with T2DM.